Psychopathy, Genes, and the Criminal Justice System - Kim, Paula (Science and Technology Law Review, 2014)
This Note examines whether, and at which stages, a criminal defendant should be permitted to offer genetic evidence of a predisposition to psychopathy. Drawing on multidisciplinary sources, including the work of legal scholars, neurobiologists, psychologists, and medical researchers, the Note discusses psychopathy, its symptoms, and how it is measured, along with the proposed genetic and environmental causes of the disorder. The Note then examines current evidence rules and trends in the admissibility of genetic evidence at the guilt/innocence phase of criminal trials and at sentencing. After discussing the potential effects of admitting evidence of a genetic basis for psychopathy at both of these phases, the Note concludes that the stigmatizing nature of the disorder and the uncertainty over its causes make it inadvisable to admit this type of evidence at the guilt/innocence phase of trial. However, admitting this evidence at sentencing is not objectionable.